The Existence of Women’s Da’wah in the Dominance and Marginalization of Patriarchal Culture - Said, Nurhidayat Muhammad; ., Mustari; ., Suhaimi; Yanti, Novi; ., Wasalmi; Nurhaidah, Siti Nuri; ., Siswandi (Journal of Ecohumanism, 2024)
This article aims to describe the existence of women’s da’wah amidst the dominance of ‘Tuan Guru’ male religious leaders’ preaching in the patriarchal culture of the Sasak community. The research was conducted in Mataram, West Nusa Tenggara, Indonesia. A qualitative descriptive method was employed for this study, utilizing data collection techniques such as interviews, observations, and documentation. This study revealed that patriarchal culture influences various aspects of Sasak society, including the religious sphere. The dominance of male religious leaders (Tuan Guru) in preaching is evident across nearly all preaching contexts. Da’wah occurs regularly and incidentally through religious lectures in prayer rooms, mosques, religious social organizations, governmental and private institutions, and utilizing mass media. Conversely, women’s da’wah through lectures has limited access; female preachers tend to engage with female communities. In terms of quantity, the number of female preachers needs to be improved compared to the number of male religious leaders. This study also identified stigmas and stereotypes associated with women in da’wah, leading to the marginalization of women in this field and restricting their emergence as preachers. The few women preachers who do emerge and deliver sermons within the community often do so with the support of their families.